THE INFLUENCE OF ACUPRESSURE ON MENSTRUAL PAIN IN FEMALE ADOLESCENT STUDENTS AT SMA NEGERI 5 BANDA ACEH - Roskianiadin, Roskianiadin; Fauziah; Fazlylawati, Ellyza (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Menstrual pain, or dysmenorrhea, is a common menstrual disorder experienced by teenage girls that can disrupt daily activities. Menstrual pain management includes, but is not limited to, pharmacological and non-pharmacological approaches. One of the non-pharmacological treatments is called acupressure. This study aims to determine the effect of acupressure therapy on the intensity of menstrual pain among female students at SMA Negeri 5 Banda Aceh. The research employed a quantitative design with a one-group pretest and posttest quasi-experimental design. The population consisted of 153 girls, and 20 of them were selected as the sample using a purposive sampling technique. The data were collected using a Numeric Rating Scale (NRS) questionnaire from May 7th to 17th, 2025. Then, the data was analyzed using the Wilcoxon Test, which obtained a p-value of 0.000 <0.05. This result indicated there was an acupressure effect on menstrual pain. Therefore, this finding proved that the use of acupressure influenced menstrual pain among female students at SMA Negeri 5 Banda Aceh. This study recommends that female students familiarize themselves with and practice acupressure techniques as an effort to reduce menstrual pain without relying on medication. Furthermore, female students need to be more open to seeking information and natural solutions for controlling reproductive health at an early age.